Short and longterm maize yield response to Mucuna pruriens and Pueraria phaseoloides relay fallow and biomass burning versus mulching in the forest zone of Southern Cameroon - Hauser, S.; Bengono, B.; Bitomo, O.E. (2008)
Maize was relay cropped with the cover crops Mucuna pruriens or Pueraria phaseoloides for between one and seven consecutive years in three sites: Ngoungoumou, located in an area of low land use intensity (LUI), about 100 km away from the next major market, and at Evendissi and Andok, in a medium LUI area, 15 to 20 km away from the next major market. Maize performance was compared with that in a natural fallow system, with fallow biomass burned versus retained as mulch in both fallow types. Fallow type had no effect on maize density. After biomass burning higher maize densities were attained at the low LUI site. Maize cob production was affected neither by fallow type nor by biomass management. Across seven years of cropping, marketable cob production in the low LUI site was 38.5% higher in mucuna fallow than in natural fallow (p < 0.06). Differences at p < 0.05 were found in one out of seven years. In the medium LUI sites, mucuna and pueraria fallow increased marketable cob production by 70–132% (p < 0.001). Maize grain yield was closely related to the marketable cob production in all sites. In the low LUI site the cumulative maize grain yield over seven years was 30% higher in mucuna fallow than in natural fallow (p < 0.07), the difference being significant at p < 0.05 in only one year. In the medium LUI sites maize grain yield was 65% higher in mucuna fallow (p < 0.001) and 69-94% higher in pueraria fallow (p < 0.001). Burning biomass had a cumulative grain yield advantage of 33% at the low LUI site (p < 0.053), with significant (p < 0.02) differences in two out of seven years. Biomass burning had no effects on maize grain yield in the medium LUI sites. No interactions between fallow type and biomass management were found. Despite the lack of frequent significant advantages of the cover crop fallows in the low LUI site, the system can be recommended because it has the potential to increase food diversity and security; in the medium LUI sites farmers were immediately convinced of the benefits of the system and have since moved on to grow high value vegetable crops.